Beating cancer‐related fatigue with the Untire mobile app: Results from a waiting‐list randomized controlled trial. Issue 11 (11th October 2020) - Spahrkäs, Simon Sebastian; Looijmans, Anne; Sanderman, Robbert; Hagedoorn, Mariët
Abstract: Objective: This waiting‐list randomized controlled trial examined the effectiveness of a self‐management mHealth app in improving fatigue and quality of life (QoL) in cancer patients and survivors. Methods: Persons with cancer‐related fatigue (CRF) were recruited across four English speaking countries, via social media, and randomized into intervention (n = 519) and control (n = 280) groups. Whereas the intervention group received immediate access to the Untire app, the control group received access only after 12‐weeks. Primary outcomes fatigue severity and interference, and secondary outcome QoL were assessed at baseline, 4, 8, and 12‐weeks. We ran generalized linear mixed models for all outcomes to determine the effects of app access (yes/no), over 12‐weeks, following the intention‐to‐treat principle. Results: Compared with the control group, the intervention group showed significantly larger improvements in fatigue severity ( d = 0.40), fatigue interference ( d = 0.35), and overall QoL on average ( d = 0.32) ( P 's < .01), but not for overall QoL in the past week ( P = .07). Sensitivity analyses indicated that participants with medium or high app use benefited most when compared with nonusers and control participants ( P 's ≤ .02). The intervention effect on fatigue interference was slightly stronger in younger participants (≤56 vs. >56). Effects did not depend on education and cancer status. Reliable change analyses indicated that significantly more people showed full recovery for fatigue in the intervention vs the control group ( P 's = .02). Conclusions: The Untire app can be an effective mHealth solution for cancer patients and survivors with moderate to severe CRF.